Аналітичні співвідношення обчислення математичного сподівання і середньої квадратичної похибки стандартно N(0, σX) розподіленої випадкової величини, підданої перетворенню √X - Kosobutsky, P. (Publishing house "Academperiodika", 2018)
The mathematical expectation and the variance have been calculated for random physical variables with the standard distribution function that are transformed by functionally related direct quadratic, X2, and inverse quadratic, √X, dependences.